2022
DOI: 10.3389/fmicb.2022.868160
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Next-Generation Sequencing vs. Traditional Pathogen Detection in the Diagnosis of Infection After Allogeneic Hematopoietic Stem Cell Transplantation in Children

Abstract: Infection is a severe complication of allo-HSCT in children, however, the accurate detection of the infection is hard. In this study, we traced the records of 101 pediatric recipients with allo-HSCT to investigate the pathogens of infection, and collected 54 bronchoalveolar lavage fluid, 32 blood, and 15 cerebrospinal fluid samples. In these samples, 87 was with post-transplant infection and 14 without infection. Using the metagenomic next-generation sequencing (mNGS) and traditional pathogen detection, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
8
2
Order By: Relevance
“…First, BALF is obtained from the respiratory tract, which is typically contaminated with normal oral flora, commensal organisms, and colonizers, leading to a relatively lower purity than blood samples and more pathogens than blood samples. 34 The initial infection site of a bloodstream infection is a lung infection, but not all pathogens of lung infections will enter the blood to cause sepsis. A study indicated that BALF mNGS was more sensitive than blood mNGS for bacterial and fungal pulmonary infections, which was consistent with research about the conventional test that the yield of BALF culture was higher than that of blood culture.…”
Section: Discussionmentioning
confidence: 99%
“…First, BALF is obtained from the respiratory tract, which is typically contaminated with normal oral flora, commensal organisms, and colonizers, leading to a relatively lower purity than blood samples and more pathogens than blood samples. 34 The initial infection site of a bloodstream infection is a lung infection, but not all pathogens of lung infections will enter the blood to cause sepsis. A study indicated that BALF mNGS was more sensitive than blood mNGS for bacterial and fungal pulmonary infections, which was consistent with research about the conventional test that the yield of BALF culture was higher than that of blood culture.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, since respiratory tract was inhabited by a polymicrobial community, sputum, and BALF samples may be contaminated with oral normal flora, commensal organisms, and colonizers, leading to a relatively lower purity than other sample types. 32 Considering the costs, adverse effects, and resistance of antimicrobial therapies, possible pathogens should be comprehensively judged by professionals based on the patient’s clinical background and other laboratory examination results. Thus, it should be noted the types of samples when interpreting the results of mNGS.…”
Section: Discussionmentioning
confidence: 99%
“…The new sequencing methods are recently applied for analysis of BAL microbiota. When comparing relative diagnostic efficiency of conventional bacterial cultures and novel metagenomic next-generation sequencing (mNGS) of BAL samples, a much higher sensitivity was revealed by analysis of different biological samples from pediatric HSCT patients by means of NGS approach, due to versatility of DNA reading technique and larger number of potentially pathogenic agents found by the multiple DNA sequencing [19]. The sensitivity of mNGS for diagnosing pulmonary infections post-transplant was 91.7 vs 22.9% by conventional testing.…”
Section: Discussionmentioning
confidence: 99%